ADDRESSING ACCOUNTABILITY DEFICITS IN COLLABORATIVE WORKING: CASE STUDY OF DISASTER MANAGEMENT IN GARUT, WEST JAVA - Yaman Suryaman (Faculty of Economics and Business, Universitas Warmadewa, 2018)
Abstract Accountability is a manifestation of good governance. It has become interesting topic to be explored by many academicians because of its complexity. Apart from the complexity, the existence of accountability mostly is assessed based on the actor who is being held to account. If the actor fails to fulfil the aims of accountability can be categorised as a lack of accountability or accountability deficits Most of literatures of accountability in collaborative working focus on regular and fixed activity. There is a need to understand this accountability deficits within the context of collaborative working in disaster management where it is very dynamic situations. This research apply qualitative research method and data collection method is executed by semi-structured interviews, observations, and document analysis in one of the most vulnerable city in Indonesia which experienced repeated flooding year. Based on this research, accountability deficits occur in all phases of disaster management; mitigation, preparedness, response, rehabilitation. Particularly, there is no specific demand of accountability among all actors and from head of task force in disaster response phase to involved actors. Victims have no power to ask for accountability to government. This is caused by victims’ belief that flooding is the fate from God. Accountability occurs only in transactional context in a formal mechanism. This occur in project based cross-sector collaborative working. Keywords: collaborative working, accountability, cross-sector collaboration, disaster management